The Biochemical Composition of Plant Raw Material of Panicum virgatum L. Varieties - Vergun, Olena; Rakhmetov, Djamal; Fishchenko, Valentyna; Rakhmetova, Svitlana; Svitlana, Oksana; Bondarchuk, Oleksandr (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
In article represented the results of a biochemical study of nine varieties and one cultivar of Panicum virgatum L. The investigations were carried out in the stage of seed ripening that is the most productive phase for these plants. Plant raw material collected and analyzed in the department of the Cultural flora of M.M. Gryshko National Botanical Garden of NAS of Ukraine. The determination of dry matter was conducted by drying to constant mass; total content of saccharides and monosaccharides – by Bertrand method in water extracts; ascorbic acid – by 2.6-dichlorophenol-indophenol titration of acid extracts; carotene – by spectrophotometric method in petrol extracts; ash – by combustion at 300–800 °C; calcium and phosphorus – by titrimetric method in acid solutions. It’s found that level of dry matter was in a range from 41.96% (Panicum virgatum f. SL-1) to 65.28% (Panicum virgatum f. RB), total content of saccharides – from 3.11% (Panicum virgatum f. RB) to 8.69% (Panicum virgatum cv. Zoriane), monosaccharides – from 1.50% (Panicum virgatum f. RR) to 6.94% (Panicum virgatum f. DB), content of ash – from 3.04% (Panicum virgatum f. RR) to 5.27% (Panicum virgatum f. SL-1), calcium – from 0.353% (Panicum virgatum f. SL-2) to 0.987% (Panicum virgatum f. PP), phosphorus – from 0.065% (Panicum virgatum f. RB) to 0.110% (Panicum virgatum f. VP), ascorbic acid – from 11.80 mg% (Panicum virgatum f. RB) to 61.94 mg% (Panicum virgatum cv. Zoriane), carotene – from 0.05 mg% (Panicum virgatum f. RB) to 1.06 mg% (Panicum virgatum f. DB). Energetic value of plant raw material was in a range from 4,102.00 Kcal/ kg (Panicum virgatum f. DB) to 4,325.41 Kcal/kg (Panicum virgatum f. RB).